Manajemen Strategi dalam Membangun Brand Image Lembaga Pendidikan di SMK Mambaul Ulum Paiton Jou - Yaqin, Muhammad Ainul; Moh Rifqoni Maulanal Qodri; Moh.Sya'roni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this research is to describe management functions, supporting factors and inhibiting factors in building the brand image of Mambaul Ulum Paiton Vocational School. This research uses a qualitative approach with the aim of describing the strategy for building the image of Mambaul Ulum Paiton Vocational School through management functions, which are composed of planning, organizing, implementing and evaluating, without the intention of drawing general conclusions or generalizations. Data collection techniques include interviews, observation, and document analysis. The research results show that planning includes setting goals/targets, needs analysis, strategy, determining resources, implementation and evaluation of planning. Organizing includes resource allocation, task assignment, determination procedures, and organizational structure. Direction involves service leadership, verbal motivation, public relations job descriptions, and policies according to planning. Monitoring and evaluation includes evaluation of success, corrective action, and solution action. Supporting factors include the achievements of the principal, staff or employees, as well as the achievements of students. Inhibiting factors include a lack of human staff, a lack of personal computer units, and a lack of budget.